The Perception and Satisfaction towards Product Appearances by Ageing Consumers - Jamalludin, Nurazlina; Majid, Ahmad Zuhairi Abdul; Hashim, Azhari Md (Science & Engineering Research Support Society, 2020)
This study proposes to suggest a course of examining product impression regarded by ageing customers. It further explores the correlation between ageing thought towards product presentation in order to entirely comprehend ways in which they will react to products as they age. A comprehensive literature revision was administered to recognize the notable, substantial findings hitherto. The collected data in this paper were collected from the secondary research method. Finally, suggestions are made as a way forward to identify the product appearance attributes and where can be considered by designers, marketers, or researchers in designing a product for ageing population. With the availability of this method, the researchers or designers, thereby can produce a quality and better product design requirement that meet the consumer needs. There is a necessity to investigate the relationship between ageing and product evolution, particularly in the presentation of the product. By recognizing the essentials of aging, it will be beneficial to marketers and designers, especially in designing a product that will fulfil their needs.